URBAN AESTHETICS: THE HARMONY OF FUNCTION, CULTURE, AND BEAUTY IN CITY DESIGN (American Journal of Research in Humanities and Social Sciences, 2025)
Urban aesthetics explores how cities express beauty, harmony, and identity through spatial organization, architecture, and cultural symbolism. The field examines the intersection of art, functionality, and human experience within the urban environment. This paper investigates the theoretical foundations of urban aesthetics, traces its historical evolution, analyzes key principles of design, and discusses contemporary challenges. By studying exemplary cities worldwide, the article reveals how aesthetic values shape human well-being, social cohesion, and environmental sustainability in urban planning.